Uji antidiabetes kombinasi ekstrak daun insulin (Tithonia diversifolia (Hems.) A.Gray) dan daun ubi jalar (Ipomoea batatas (L.) Lam) ungu pada tikus jantan akibat induksi streptozotocin - Octavianing Yosephine; Galih Samodra; Khamdiyah Indah Kurniasih (Journal of Pharmaceutical and Sciences, 2023)
Diabetes mellitus is a condition in which blood glucose levels are high enough in the body. Insulin leaves contain tannins, flavonoids and saponins which play a role in fighting free radicals. Purple sweet potato leaves have anthocyanin and phenolic flavonoid compounds that function as anti-diabetics. The combination of the two is expected to produce a synergistic effect to increase the effectiveness of antidiabetics. This research aims to find out the antidiabetic effect and the effective dose of a combination of insulin leaf extract and purple sweet potato leaves. This study used 25 rats as test animals which were divided into 5 groups. The blood glucose levels of the rats were measured using the GOD-PAP method. The results showed that the combination dose of insulin leaf ethanol extract 30 mg/kgBB and purple sweet potato leaves 120 mg/kgBB (combination group 2) had an anti-diabetic effect, an average of 97.49 and a positive control (glibenclamide) mean of 116.83 in reducing blood glucose levels in streptozotocin-induced mice. The research show that based on the One Way ANOVA analysis, the sig. ie 0.000 <0.05, then in conclusion the average of the five test groups has a significant difference.